2019
DOI: 10.3390/genes10020096
|View full text |Cite
|
Sign up to set email alerts
|

Translation of Human β-Actin mRNA is Regulated by mTOR Pathway

Abstract: The mammalian target of rapamycin (mTOR) kinase is a well-known master regulator of growth-dependent gene expression in higher eukaryotes. Translation regulation is an important function of the mTORC1 pathway that controls the synthesis of many ribosomal proteins and translation factors. Housekeeping genes such as β-actin (ACTB) are widely used as negative control genes in studies of growth-dependent translation. Here we demonstrate that translation of both endogenous and reporter ACTB mRNA is inhibited in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 57 publications
3
13
0
Order By: Relevance
“…Instead, it is possible that mTORC1 controls translation initiation and local mRNA transport ( Pilaz et al, 2016 ; Pilaz and Silver, 2017 ) into the basal processes of oRG cells. Recent studies have identified direct regulation of translation of the human ß-Actin mRNA by mTORC1 and shown that this regulation may be cell-type dependent ( Eliseeva et al, 2019 ). mTORC1 may therefore, indirectly affect the ability of oRGs to generate cytoskeletal proteins needed for basal process elongation and maintenance by regulating protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, it is possible that mTORC1 controls translation initiation and local mRNA transport ( Pilaz et al, 2016 ; Pilaz and Silver, 2017 ) into the basal processes of oRG cells. Recent studies have identified direct regulation of translation of the human ß-Actin mRNA by mTORC1 and shown that this regulation may be cell-type dependent ( Eliseeva et al, 2019 ). mTORC1 may therefore, indirectly affect the ability of oRGs to generate cytoskeletal proteins needed for basal process elongation and maintenance by regulating protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…mTORC1 and C2 act in large multi-protein complexes to control both aspects of protein regulation. As a result, optimum levels of individual proteins are needed for the proper assembly of functional complexes ( Ardestani et al, 2018 ; Eliseeva et al, 2019 ; Varusai and Nguyen, 2018 ). It is probable that too much or too little of any of the individual proteins will result in abnormal functional protein assemblies and disrupted cytoskeleton in oRG cells.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, it is possible that mTORC1 controls translation initiation and local mRNA transport (Pilaz et al, 2016;Pilaz & Silver, 2017) into the basal processes of oRG cells. Recent studies have identified direct regulation of translation of the human ß-Actin mRNA by mTORC1 and shown that this regulation may be cell-type dependent (Eliseeva et al, 2019). mTORC1 may therefore, indirectly affect the ability of oRGs to generate cytoskeletal proteins needed for basal process elongation and maintenance by regulating protein synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…mTORC1 and C2 act in large multi-protein complexes to control both aspects of protein regulation. As a result, optimum levels of individual proteins are needed for the proper assembly of functional complexes (Ardestani et al, 2018;Eliseeva et al, 2019;Varusai & Nguyen, 2018). It is probable that too much or too little of any of the individual proteins will result in abnormal functional protein assemblies and disrupted cytoskeleton in oRG cells.…”
Section: Discussionmentioning
confidence: 99%
“…Plasmids pSpCas9(BB)-2A-Puro (a gift from Feng Zhang; Addgene plasmid #48,139) [45], pcDNA3-HA-YB-1 and pcDNA3-HA [5], pGFP-c3 [46], pNL2.2 SLU7-NlucP [47], pSP36TLuc-A50 [48], pcDNA-3.1-puro (kindly provided by Dr. Dmitriev, A.N. Belozersky Institute of Physico-Chemical Biology, MSU).…”
Section: Methodsmentioning
confidence: 99%